From Practice to Metaphysics: The Evolution of Spiritual Stations in Ibn ‘Arabī’s Thought - Aljahsh, Muhammad Ahmad Ibrahim (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2025)
Classical Sufi manuals present the spiritual stages achieved through disciplined Sufi practice. This article argues that the seventh/thirteenth-century mystic Muh}yī al-Dīn Ibn ‘Arabī reimagined the spiritual stations as ontological realities rather than behavioral achievements. Through a systematic reading of the twenty-second chapter of his Meccan Revelations in dialogue with his fellow Sufi gnostics, it shows that Ibn ʿArabī recast sequential progress into metaphysical loci of divine self-disclosure. The analysis identifies a triadic architecture of cosmic, spiritual, and ontological stations, where the stations function as a holographically interlinked field rather than a linear ladder. This reframing marks the transition from a “first mystical tradition” centered on ethical discipline to a “second mystical tradition” oriented by ontological insight. The conclusion sketches implications for Islamic metaphysics, including the Sadrian synthesis, and suggests how the Akbarian model offers transferable tools for comparative work on mystical experience across traditions.